2022
DOI: 10.1111/psj.12475
|View full text |Cite
|
Sign up to set email alerts
|

Taking perspective of the stories we tell about transgender rights: The narrative policy framework

Abstract: Our project uses the narrative policy framework (NPF) to explore narrative effects on attitudes about transgender rights. The framework focuses on the stories that are told about public policy. As opposed to conceptualizing communications as informational, NPF suggests that getting lost in the story is primary for attitude change. We also incorporate a perspective taking exercise to examine its effects on individual attitudes. Using an experiment on 1784 American adults, we found that individuals who received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…As Murib (2020) explains of legislation like HB2, “laws that seek to reinforce sex‐segregated public spaces not only impose dominant ideas about sex as biological and gender as binary, but also construct and reinforce ideas about who is and is not allowed in public space” (p. 159). Conveying social constructions such as these has been shown to influence the broader public's support for transgender rights (Flores et al., 2022; Turnbull‐Dugarte & McMillan, 2022). HB2 also may have altered how people targeted by the bill evaluate their political efficacy and trust in government.…”
Section: Preemption Feedback In Actionmentioning
confidence: 99%
“…As Murib (2020) explains of legislation like HB2, “laws that seek to reinforce sex‐segregated public spaces not only impose dominant ideas about sex as biological and gender as binary, but also construct and reinforce ideas about who is and is not allowed in public space” (p. 159). Conveying social constructions such as these has been shown to influence the broader public's support for transgender rights (Flores et al., 2022; Turnbull‐Dugarte & McMillan, 2022). HB2 also may have altered how people targeted by the bill evaluate their political efficacy and trust in government.…”
Section: Preemption Feedback In Actionmentioning
confidence: 99%
“…GAC has become one of the battles in the ongoing and intensifying political culture war in the U.S. (Castle, 2019; Jacoby, 2014) and remains a policy arena wrought with disinformation (Crasnow, 2021; Family Research Council , 2022; Turnbull‐Dugarte & McMillan, 2022). GAC policies are also relatively nascent from a policy studies perspective, however attention on gender identity policies is growing (Flores et al., 2022; McMahon, 2023; SoRelle & Fullerton, 2024; Taylor & Lewis, 2014; Turnbull‐Dugarte & McMillan, 2022).…”
Section: Case Backgroundmentioning
confidence: 99%
“…GAC policies are relatively nascent policy issues nested within the broader literature of transgender and gender identity studies found in policy and political sciences (Billard, 2019; Flores et al., 2022; Haider‐Markel et al., 2019; Lewis et al., 2022; McMahon, 2023; Murib, 2023; Taylor & Haider‐Markel, 2014; Turnbull‐Dugarte & McMillan, 2022; Wright et al., 2021) and troves of literature on GAC from medical and psychological studies (Boskey et al., 2019; Padula & Baker, 2017; Safer et al., 2016). The study of GAC relates to the scholarship on emotions in anti‐gender movements in Europe (Crasnow, 2021; Graff & Korolczuk, 2022; Hsu, 2022), social movements both broadly (Clarke et al., 2006) in contexts of LGBTQ+ studies (Cannon, 2022; Currah, 2022; Currah et al., 2006; Haider‐Markel & Joslyn, 2013; Lewis, 2011), and dramaturgical and structural theories from the sociology of emotion (Stets & Turner, 2014; Turner & Stets, 2005) as these theories have direct connections to beliefs, coalition strategies, and gender policies.…”
Section: Introductionmentioning
confidence: 99%
“…In their article, "Taking Perspective of the Stories We Tell about Transgender Rights: The Narrative Policy Framework," Flores et al (2023) utilize the NPF to examine how narratives shape our attitudes regarding transgender rights. Rather than considering communications as just informative, the NPF stresses that becoming engaged in stories is essential for shifting attitudes when it comes to public policy.…”
Section: Editorial Introduction: Contributing To the Policy Process L...mentioning
confidence: 99%